Crisis Planning for Online Students: Lessons Learned from a Major Disruption - Holzweiss, Peggy C; Walker, Daniel W; Chisum, Ruth; Sosebee, Thomas (Online Learning, 2020)
While institutions have crisis management plans, they are often focused on face-to-face students and the physical campus. In this case study, researchers investigated the crisis response for online students at one institution after Hurricane Harvey hit the Houston, Texas, area in the fall of 2017. While face-to-face students were not severely impacted, more than a thousand online students were in the impact zone and in danger of dropping out. With financial resources and student retention at risk, campus leaders approved a strategy to delay online courses for several weeks. This study examines the experiences of the front-line staff who implemented the plan. Findings suggest that institutions need a proactive crisis plan for online students that includes understanding where this population resides, how different campus units can provide support in a crisis, who should lead the crisis response, and what kind of care can be offered to the front-line responders during the crisis period.